Extracción de pectina a partir del desecho de sandía (Citrillus lanatus); y elaboración de mermelada de pomarrosa (Syzygium malaccense) - Vasquez Garcia, Marcos Gabriel (2024)
The Peruvian Amazon is diverse due to the large number of tropical fruits such as the regional watermelon and the pomarrosa, being the objective of the study to obtain and extract pectin with all its parameters: temperature, time, pH, and yield and its use in the production of jam, for the extraction of pectin hydrochloric acid was used as a reagent. at 1 N, exactly 20 drops at pH: 1.00, treatment time of 60 minutes and a temperature of 95oC, for the separation/precipitation of pectin, 96% ethanol was used, obtaining yield results of 0.14%, compared to 5,560 kg, of watermelon rind, having a humidity; 4.22%, ash: 2.67%, free acid (meq. free carbonates), methoxyl content: 2.50% expressed in galacturonic acid), being in product classified as acid pectin with low methoxyl content, the second part of the research consisted of obtaining a jam using that pectin obtained, for which the following flow was followed: raw material, reception, weighing, selection, classification, washing, blanching, pulping/refining, formulation mixing, heat treatment, pectin addition, packaging, cooling, storage and final product, for which a sensory evaluation of the five proposed formulations was carried out, concluding that the fifth is the one that meets the requirements of the NTP 203.047 Standard. In 2017, both in the physical, chemical, microbiological and the important sensory analysis, color, odor, taste and general appearance were evaluated by 25 trained panelists, statistically there is no significant difference.